Hyper-Cross-Linked Polyacetylene-Type Microporous Networks Decorated with Terminal Ethynyl Groups as Heterogeneous Acid Catalysts for Acetalization and Esterification Reactions - Sekerová, Lada; Lhotka, Miloslav; Vyskočilová, Eliška; Faukner, Tomáš; Slováková, Eva; Brus, Jiří; Červený, Libor; Sedláček, Jan (Chemistry (Weinheim an der Bergstrasse, Germany), 2018)
Heterogeneous catalysts based on materials with permanent porosity are of great interest owing to their high specific surface area, easy separation, recovery, and recycling ability. Additionally, porous polymer catalysts (PPCs) allow us to tune catalytic activity by introducing various functional centres. This study reports the preparation of PPCs with a permanent micro/mesoporous texture and a specific surface area SBET of up to 1000 m2 g-1 active in acid-catalyzed reactions, namely aldehyde and ketone acetalization and carboxylic acid esterification. These PPC-type conjugated hyper-cross-linked polyarylacetylene networks were prepared by chain-growth homopolymerization of 1,4-diethynylbenzene, 1,3,5-triethynylbenzene and tetrakis(4-ethynylphenyl)methane. However, only some ethynyl groups of the monomers (from 58 to 80 %) were polymerized into the polyacetylene network segments while the other ethynyl groups remained unreacted. Depending on the number of ethynyl groups per monomer molecule and the covalent structure of the monomer, PPCs were decorated with unreacted ethynyl groups from 3.2 to 6.7 mmol g-1 . The hydrogen atoms of the unreacted ethynyl groups served as acid catalytic centres of the aforementioned organic reactions. To the best of our knowledge, this is first study describing the high activity of hydrogen atoms of ethynyl groups in acid-catalyzed reactions.
Keywords: acetalization; polyacetylenes; microporous polymers; hyper-cross-linked polymers; porous polymer catalysts